2010
DOI: 10.1093/neuonc/noq176
|View full text |Cite
|
Sign up to set email alerts
|

APO010, a synthetic hexameric CD95 ligand, induces human glioma cell death in vitro and in vivo

Abstract: Death receptor targeting has emerged as one of the promising novel approaches of cancer therapy. The activation of one such prototypic death receptor, CD95 (Fas/APO-1), has remained controversial because CD95 agonistic molecules have exhibited either too strong toxicity or too little activity. The natural CD95 ligand (CD95L) is a cytokine, which needs to trimerize to mediate a cell death signal. Mega-Fas-Ligand, now referred to as APO010, is a synthetic hexameric CD95 agonist that exhibits strong antitumor act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 33 publications
1
37
0
Order By: Relevance
“…Previously published studies have shown several approaches to target FAS/FAS ligand signaling for cancer therapy, including administration of FAS agonist antibodies or FAS ligand recombinant proteins (2226), FAS ligand gene therapy (2729) or use of chemotherapeutic drugs to induce FAS or FAS ligand expression (3032). Here, to overcome radioresistance in SUM159 and HCC1954 tumors, we hypothesized that activating FAS signaling with radiation may have a synergistic apoptotic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published studies have shown several approaches to target FAS/FAS ligand signaling for cancer therapy, including administration of FAS agonist antibodies or FAS ligand recombinant proteins (2226), FAS ligand gene therapy (2729) or use of chemotherapeutic drugs to induce FAS or FAS ligand expression (3032). Here, to overcome radioresistance in SUM159 and HCC1954 tumors, we hypothesized that activating FAS signaling with radiation may have a synergistic apoptotic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Agonist antibodies targeting FAS, or FASL expressed through adenoviral vector transfer, have shown antitumour activity in murine models, although this approach has been associated with hepatotoxicity and has therefore generated less interest than TRAILR-targeting antibodies 184 . Alternative reagents that might exhibit agonistic activity but low toxicity have been pursued, and a recombinant hexameric form of FASL (APO010) was found to reduce tumour survival in vitro and in animal tumour models 185,186 . A Phase I trial of APO010 was planned in 2007 in patients with solid tumours but the study was not carried out.…”
Section: Targeting Tnfsf Molecules In Cancermentioning
confidence: 99%
“…Moreover, TNF failed to achieve durable responses, and eventually was abandoned from further clinical development beyond efforts that have continued for regional targeting of localized disease. Fas ligand (Apo1 ligand) was discovered as a putative anti-cancer drug development approach but was also abandoned [33,34]. A Fas receptor agonistic antibody strategy was developed, but discontinued from development after massive apoptosis in hepatocytes.…”
Section: Trail Agentsmentioning
confidence: 99%